2015
DOI: 10.1007/s10552-015-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Africa’s oesophageal cancer corridor: Do hot beverages contribute?

Abstract: Purpose Hot beverage consumption has been linked to oesophageal squamous cell cancer (EC) but its contribution to the poorly-understood East African EC corridor is not known. Methods In a cross-sectional study of general-population residents in Kilimanjaro, North Tanzania, tea drinking temperatures and times were measured. Using linear regression models, we compared drinking temperatures to those in previous studies, by socio-demographic factors and tea type (“milky tea” which can be 50% or more milk and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 30 publications
4
50
1
Order By: Relevance
“…One was the convenience sampling of hospital visitors, which led to a relatively young age distribution in the study population. In our analysis, however, preferred tea temperature was not related to age (p=0.73).The sample size was also relatively small compared to the study by Munishi et al, which had twice as many subjects 23 . There were also limitations to our method of temperature assessment.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…One was the convenience sampling of hospital visitors, which led to a relatively young age distribution in the study population. In our analysis, however, preferred tea temperature was not related to age (p=0.73).The sample size was also relatively small compared to the study by Munishi et al, which had twice as many subjects 23 . There were also limitations to our method of temperature assessment.…”
Section: Discussioncontrasting
confidence: 75%
“…We reviewed the literature for other studies of preferred beverage temperature 16–18,23,3140 (Table 4), and found that the mean preferred tea temperature in our study was 1.5°C higher than any other studied population. It should be noted that the various studies presented in Table 4 use various methodologies to assess temperature and this limits the ability to compare them, and numerous studies concerning beverage temperature do not report descriptive statistics for temperature.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A South African study showed increased ESCC risk associated with daily tea consumption, though temperatures were not measured . Further, hot beverage consumption is prevalent in the Kilimanjaro region of Tanzania where the average temperature at first sip was 71°C, which correlated with a self‐reported history of tongue burning . These tea temperatures far exceeded those in Iran where a strong tea temperature‐ESCC association was observed (odds ratio 8 for very hot vs. warm/lukewarm tea) .…”
Section: Resultsmentioning
confidence: 98%